The Multifarious Function of Medical Records: Ethical Issues - Papagounos, G.; Spyropoulos, B. (Methods of Information in Medicine, 1999)
Medical records comprise history data, physical examination, biosignals, data acquired through in vitro diagnostic tests, images, therapeutic data, and administrative data. Beyond the use of records for therapy, they are also used in research, teaching, the allocation of resources, and for the construction of the patient’s personal history. These functions give rise to a number of important ethical issues. The most important ethical issues are the patient’s autonomy in decisions pertaining to proposed therapeutic interventions, the confidentiality of the information contained in the records, the reliability of the information for research, and questions related to healthcare policy and the distribution of healthcare resources.
Keywords: Patient Records; Ethics; Technology; Interests